Analysis of Base and Leading Sectors in Accelerating Development in Wakatobi Regency - Nur, Muh.; Supriaddin, Nofal; Kalsum, Ummy; Masitha, Zainab; Salleh, Mad Ithnin bin (Advances In Social Humanities Research, 2025)
This research activity will be carried out as an effort to assist the Wakatobi Regency government in solving economic problems based on efforts to increase the output of economic commodities that are categorized as basic and increase the output of regional leading economic sectors so that they are able to contribute more to the acquisition of the Gross Domestic Product (GRDP) of the Wakatobi Regency area. This study aims to obtain and analyze: The results of the identification of economic commodities that fall into the base category to be developed in the Wakatobi Regency area. The results of the identification of leading economic sectors that fall into the basic category to be developed in the Wakatobi Regency area. The results of the development of basic and leading economic sectors in accelerating economic growth in Wakatobi Regency. This research uses Location Quotient (LQ) analysis and Revealed Comparative Advantage (RCA) analysis as well as regression analysis with a simple linear regression model. This research is expected to show that the development of basic economic commodities and regional leading economic sectors can accelerate the growth rate of GRDP in the process of regional economic development in Wakatobi Regency. The results showed that: (1). The results of the identification of economic commodities that fall into the basic category to be developed in the Wakatobi Regency area are: Plantation crop commodities, food crop commodities, fruit crop commodities, vegetable crop commodities, vegetable crop commodities harvested at once, large livestock meat commodities, livestock meat commodities, poultry meat commodities, marine fisheries commodities, aquaculture commodities. (2) Identification of economic sectors from the leading economic sectors that fall into the basic category to be developed in the Wakatobi Regency area are the agricultural, livestock, forestry and fisheries economic sectors; construction sector; wholesale and retail trade sector; car and motorcycle repair; real estate sector; government administration, defense and social security sector and other service sectors. (3) The development of basic and leading regional economic sectors can accelerate economic growth in Wakatobi Regency as evidenced by the contribution of basic and leading regional economies that have a positive and significant effect on increasing regional economic growth in Wakatobi Regency.